Method for improving drawing performance of tire cord steel through Cr alloying
By adding Cr elements to the cord steel and replacing the C and Mn elements in part, the tough plasticity of cord steel is improved, and the problems of low pulling performance and high wire breaking rate of existing cord steel are solved, thereby achieving higher tensile strength and lower wire breaking rate.
Patent Information
- Application Number
- CN202510100458.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-05-02
AI Technical Summary
During the production process of existing cord steel, the pulling performance is low, resulting in high wire breakage rate and difficult to ensure production efficiency and quality.
By adding Cr elements to the cord steel, replacing part of C and Mn elements, the tough plasticity of the steel is improved, thereby improving the pulling performance of the cord steel.
The tensile strength and cross-section shrinkage rate of cord steel are significantly improved, the wire breakage rate of the drawing process is reduced, and the production efficiency and product quality are improved.
Smart Images

Figure BDA0005254056140000051 
Figure BDA0005254056140000061
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cord steel production, and in particular to a method for improving the drawing performance of cord steel by Cr alloying. Background Art
[0002] Cord steel wire rod is a high-quality wire product with high tensile strength and good toughness. It is mainly used to process automobile tire radials (commonly known as steel cords), which can improve the safety, wear resistance and fatigue resistance of tires. Tires made of cord steel are more durable and stable than conventional tires, and have higher safety performance. Since the French Michelin company invented the automobile radial tire in the late 1940s, steel cord has been the most promising rubber skeleton material.
[0003] At present, the steel cord production process at home and abroad adopts The wire rod for steel cord undergoes multiple drawing processes such as primary drawing, intermediate drawing, wet drawing, etc. First, the wire rod is drawn to After heat treatment to eliminate work hardening, it is pulled to In order to obtain the required mechanical properties, metallographic structure and coating quality, it is also necessary to undergo lead bath isothermal quenching and brass electroplating, and finally wet drawing to The length of the wire after drawing is more than 1000 times the length of the wire rod, and the total area reduction rate is as high as over 99%; in the subsequent twisting and stranding process, it also undergoes a series of deformation processes such as bending and torsion; therefore, steel cord is also one of the most difficult metal products to produce.
[0004] Steel cord is the best among wire products and is known as the "crown jewel". The steel wires are made into steel ropes, and no breakage is allowed within 100 km during the process of drawing them into filaments. Therefore, all production processes of steel cords have strict requirements.
[0005] The main factors affecting steel cord breakage are as follows: 1) Control of residual elements and harmful elements; 2) Control of total oxygen content; 3) Control of segregation; 4) Control of gas content; 5) Control of inclusions; 6) Control of microstructure; 7) Control of decarburization layer, etc.
[0006] In summary, the drawing performance of cord steel is an important indicator to reduce the wire breakage rate in the cord steel processing process, improve production efficiency, and test the quality level of cord steel.
[0007] The Chinese patent application with application number CN201210149187.2 discloses "a microalloyed cord steel wire rod with large strain drawing performance", whose chemical composition and mass percentage are: C is 0.65-0.85%, Si is 0.15-0.25%, Mn is 0.48-0.58%, P≤0.015%, S≤0.020%, Ti≤0.0010%, Al≤0.0050%, O≤0.0030%, N≤0.0060%, and the balance is microalloying elements and Fe; the microalloying elements: two or three of Cr is 0.1-0.50%, V is 0.05-0.20% and Co is 0.10-0.50%. The cord steel wire rod produced by the invention has a tensile strength of 1150-1250MPa, a cross-sectional shrinkage of 39-45%, and a GBC grade of A or B. After being subjected to a sorbitization treatment, the wire rod can be continuously drawn to a true strain of 4.92, and the tensile strength of the steel cord filament reaches 3500-4000MPa, the number of fracture torsion is 60-70, and the wire breakage rate is 1.5-2.1 times / ton. However, the chemical composition thereof adopts a binary or ternary composite alloy design of Cr, V, and Co, which is significantly different from the present invention. Summary of the invention
[0008] The present invention provides a method for improving the drawing performance of cord steel by Cr alloying, wherein a certain amount of Cr element is added to replace part of C and Mn to improve the toughness and plasticity of the steel, thereby improving the drawing performance of the cord steel; by adding the Cr element and appropriately reducing the content of C and Mn elements, the toughness and plasticity of the cord steel are greatly improved, and the wire breakage rate in the drawing process is greatly reduced.
[0009] In order to achieve the above object, the present invention adopts the following technical solutions:
[0010] A method for improving the drawing performance of cord steel by Cr alloying, for cord steel of grade 70 to grade 95, by increasing the Cr content in the steel and reducing the C content and the Mn content, the strength, toughness and drawing performance of the cord steel are improved; the composition of the cord steel is specifically as follows in terms of mass percentage:
[0011] LX70ACr cord steel, C: 0.65% ~ 0.72%, Si: 0.15% ~ 0.30%; Mn: 0.20% ~ 0.60%; Cr: 0.15% ~ 0.50%; P ≤ 0.025%; S ≤ 0.015%; the balance is Fe and unavoidable impurities;
[0012] LX70BCr cord steel, C: 0.65% ~ 0.72%; Si: 0.15% ~ 0.30%; Mn: 0.20% ~ 0.60%; Cr: 0.15% ~ 0.50%; P ≤ 0.020%; S ≤ 0.010%; the balance is Fe and unavoidable impurities;
[0013] LX80ACr cord steel, C: 0.72% ~ 0.82%; Si: 0.15% ~ 0.30%; Mn: 0.20% ~ 0.60%; Cr: 0.15% ~ 0.50%; P ≤ 0.025%; S ≤ 0.015%; the balance is Fe and unavoidable impurities;
[0014] LX80BCr cord steel, C: 0.72% ~ 0.82%; Si: 0.15% ~ 0.30%; Mn: 0.20% ~ 0.60%; Cr: 0.15% ~ 0.50%; P ≤ 0.020%; S ≤ 0.010%; the balance is Fe and unavoidable impurities;
[0015] LX85BCr cord steel, C: 0.82% ~ 0.86%; Si: 0.15% ~ 0.30%; Mn: 0.20% ~ 0.60%; Cr: 0.15% ~ 0.50%; P ≤ 0.020%; S ≤ 0.010%; the balance is Fe and unavoidable impurities;
[0016] LX90BCr cord steel, C: 0.86% ~ 0.92%; Si: 0.15% ~ 0.30%; Mn: 0.20% ~ 0.60%; Cr: 0.15% ~ 0.50%; P ≤ 0.020%; S ≤ 0.010%; the balance is Fe and unavoidable impurities;
[0017] LX96BCr cord steel: C: 0.92% ~ 0.96%; Si: 0.15% ~ 0.30%; Mn: 0.20% ~ 0.60%; Cr: 0.15% ~ 0.50%; P ≤ 0.015%; S ≤ 0.010%; the balance is Fe and unavoidable impurities.
[0018] The properties of the LX70ACr cord steel are as follows: tensile strength of 1000-1120 MPa, elongation ≥10%, and cross-sectional shrinkage ≥40%.
[0019] The properties of the LX70BCr cord steel are as follows: tensile strength of 1000-1120 MPa, elongation ≥10%, and cross-sectional shrinkage ≥40%.
[0020] The properties of the LX80ACr cord steel are as follows: tensile strength of 1120-1250 MPa, elongation ≥10%, and cross-sectional shrinkage ≥38%.
[0021] The properties of the LX80BCr cord steel are as follows: tensile strength of 1120-1250 MPa, elongation ≥10%, and cross-sectional shrinkage ≥38%.
[0022] The properties of the LX85BCr cord steel are as follows: tensile strength ≥1127MPa, elongation ≥6%, and cross-sectional shrinkage ≥30%.
[0023] The properties of the LX90BCr cord steel are as follows: tensile strength ≥ 1130 MPa, elongation ≥ 5%, and cross-sectional shrinkage ≥ 25%.
[0024] The properties of the LX96BCr cord steel are as follows: tensile strength ≥ 1150 MPa, elongation ≥ 5%, and cross-sectional shrinkage ≥ 25%.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1) A certain amount of Cr is added to the steel of the present invention to replace part of the C and Mn elements, so as to improve the toughness and plasticity of the steel, and then improve the drawing performance of the cord steel; Studies have shown that adding a certain amount of Cr to high carbon steel can effectively reduce the transformation temperature of supercooled austenite, reduce the formation of grain boundary cementite, refine the spacing between pearlite lamellae, and reduce the probability of the appearance of network carbon structure, thereby improving the toughness and plasticity of the steel; Related research data show that for every 0.01% increase in the chromium content, the tensile strength of the steel increases by 3.22MPa and the cross-sectional shrinkage rate increases by 0.078%. At the same time, since a certain amount of Cr is added to replace part of the C and Mn elements, that is, the mass fraction of C and Mn in the steel is reduced, the segregation of molten steel during the solidification process and the surface decarburization reaction of the steel during the heating process can be reduced; In addition, reducing the carbon content in the wire rod and increasing the Cr content can inhibit the dissolution of cementite during the drawing process, and further improve the drawing performance of the steel;
[0027] 2) By adding Cr and appropriately reducing the content of C and Mn elements, the toughness and plasticity of the cord steel are greatly improved, and the wire breakage rate during the drawing process is greatly reduced.
[0028] 3) Taking LX80ACr cord steel as an example, compared with cord steel products of the same grade, the cord steel produced by the present invention has an original strength of 50Mpa after rolling and an area reduction rate of 4.9%. The LX80ACr cord steel wire rod is drawn into a diameter after pretreatment, rough drawing and other processes. The semi-finished steel wire is then drawn into a diameter of The strength of the finished steel wire can reach more than 3800Mpa. Compared with the conventional products of the same level, the average tensile strength is increased by 300-400Mpa; under the same process conditions, the wire breakage rate is reduced by more than 40%. DETAILED DESCRIPTION
[0029] The method for improving the drawing performance of cord steel by Cr alloying of the present invention improves the strength, toughness and drawing performance of cord steel of grade 70 to grade 95 by increasing the Cr content in the steel and reducing the C content and the Mn content; the components of the cord steel are specifically as follows in terms of mass percentage:
[0030] LX70ACr cord steel, C: 0.65% ~ 0.72%, Si: 0.15% ~ 0.30%; Mn: 0.20% ~ 0.60%; Cr: 0.15% ~ 0.50%; P ≤ 0.025%; S ≤ 0.015%; the balance is Fe and unavoidable impurities;
[0031] LX70BCr cord steel, C: 0.65% ~ 0.72%; Si: 0.15% ~ 0.30%; Mn: 0.20% ~ 0.60%; Cr: 0.15% ~ 0.50%; P ≤ 0.020%; S ≤ 0.010%; the balance is Fe and unavoidable impurities;
[0032] LX80ACr cord steel, C: 0.72% ~ 0.82%; Si: 0.15% ~ 0.30%; Mn: 0.20% ~ 0.60%; Cr: 0.15% ~ 0.50%; P ≤ 0.025%; S ≤ 0.015%; the balance is Fe and unavoidable impurities;
[0033] LX80BCr cord steel, C: 0.72% ~ 0.82%; Si: 0.15% ~ 0.30%; Mn: 0.20% ~ 0.60%; Cr: 0.15% ~ 0.50%; P ≤ 0.020%; S ≤ 0.010%; the balance is Fe and unavoidable impurities;
[0034] LX85BCr cord steel, C: 0.82% ~ 0.86%; Si: 0.15% ~ 0.30%; Mn: 0.20% ~ 0.60%; Cr: 0.15% ~ 0.50%; P ≤ 0.020%; S ≤ 0.010%; the balance is Fe and unavoidable impurities;
[0035] LX90BCr cord steel, C: 0.86% ~ 0.92%; Si: 0.15% ~ 0.30%; Mn: 0.20% ~ 0.60%; Cr: 0.15% ~ 0.50%; P ≤ 0.020%; S ≤ 0.010%; the balance is Fe and unavoidable impurities;
[0036] LX96BCr cord steel: C: 0.92% ~ 0.96%; Si: 0.15% ~ 0.30%; Mn: 0.20% ~ 0.60%; Cr: 0.15% ~ 0.50%; P ≤ 0.015%; S ≤ 0.010%; the balance is Fe and unavoidable impurities;
[0037] The properties of the LX70ACr cord steel are as follows: tensile strength of 1000-1120 MPa, elongation ≥10%, and cross-sectional shrinkage ≥40%.
[0038] The properties of the LX70BCr cord steel are as follows: tensile strength of 1000-1120 MPa, elongation ≥10%, and cross-sectional shrinkage ≥40%.
[0039] The properties of the LX80ACr cord steel are as follows: tensile strength of 1120-1250 MPa, elongation ≥10%, and cross-sectional shrinkage ≥38%.
[0040] The properties of the LX80BCr cord steel are as follows: tensile strength of 1120-1250 MPa, elongation ≥10%, and cross-sectional shrinkage ≥38%.
[0041] The properties of the LX85BCr cord steel are as follows: tensile strength ≥1127MPa, elongation ≥6%, and cross-sectional shrinkage ≥30%.
[0042] The properties of the LX90BCr cord steel are as follows: tensile strength ≥ 1130 MPa, elongation ≥ 5%, and cross-sectional shrinkage ≥ 25%.
[0043] The properties of the LX96BCr cord steel are as follows: tensile strength ≥ 1150 MPa, elongation ≥ 5%, and cross-sectional shrinkage ≥ 25%.
[0044] The strength index of cord steel is relatively high, and generally a high content of carbon is added to ensure the final strength of the steel. However, a high carbon content in the steel will lead to segregation during the casting process, as well as many problems such as the control of the carbon network structure and decarburization layer during the rolling cooling process. Studies have shown that alloying high-carbon steel wire rods with Cr elements can significantly improve the structure and properties of the material. Cr alloying can effectively inhibit the precipitation of the proeutectoid phase and increase the sorbitization rate. Adding chromium elements to high-carbon steel can significantly increase the tensile strength while increasing the cross-sectional shrinkage rate, improve the toughness of the material, and thus improve the drawing performance of the material.
[0045] The invention mainly relates to 70-95 grade cord steel products, and achieves the purpose of improving the strength, toughness and drawing performance of the cord steel by increasing the Cr content by 0.15%-0.35% on the basis of the original component system and appropriately reducing the content of C and Mn elements.
[0046] The method of improving the drawing performance of cord steel by Cr alloying described in the present invention includes component design and production process, and the production process includes but is not limited to converter and electric furnace smelting, LF furnace refining, RH vacuum treatment and continuous casting process; the main difference from the conventional production process is that Cr alloying and composite addition of other alloy elements are carried out during the smelting and refining process.
[0047] In order to more intuitively embody the present invention, the embodiments of the present invention are further described in conjunction with examples. The following examples are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any technical solution that can be obviously obtained by a person skilled in the art within the technical scope disclosed in the present invention, including simple changes or equivalent replacements, is within the protection scope of the present invention.
[0048] [Example]
[0049] The main chemical components of the cord steel of each embodiment are shown in Table 1, and the properties of the cord steel of each embodiment are shown in Table 2.
[0050] Table 1 Main chemical components in steel / %
[0051] Example Cord steel grade C Si Mn Cr P S 1 LX70ACr 0.68 0.22 0.47 0.39 0.012 0.008 2 LX70BCr 0.66 0.19 0.33 0.41 0.010 0.006 3 LX80ACr 0.78 0.27 0.52 0.38 0.021 0.009 4 LX80BCr 0.77 0.26 0.34 0.29 0.014 0.010 5 LX85BCr 0.84 0.19 0.47 0.33 0.016 0.005 6 LX90BCr 0.89 0.25 0.41 0.36 0.014 0.007 7 LX96BCr 0.94 0.28 0.53 0.44 0.011 0.008
[0052] Table 2 Cord steel properties
[0053]
[0054]
[0055] The above embodiments prove that after adopting the method of the present invention, under the same process conditions, by adding a certain content of Cr element to replace part of the C and Mn elements, a more excellent microstructure can be obtained, the strength and toughness of the cord steel can be improved, and then the drawing performance of the cord steel can be improved.
[0056] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for improving the drawing performance of cord steel by Cr alloying, characterized in that: For cord steels of grade 70 to grade 95, the strength, toughness and drawing properties of the cord steel are improved by increasing the Cr content in the steel and reducing the C content and Mn content; the composition of the cord steel is as follows in terms of mass percentage: LX70ACr cord steel, C: 0.65% ~ 0.72%, Si: 0.15% ~ 0.30%; Mn: 0.20% ~ 0.60%; Cr: 0.15% ~ 0.50%; P ≤ 0.025%; S ≤ 0.015%; the balance is Fe and unavoidable impurities; LX70BCr cord steel, C: 0.65% ~ 0.72%; Si: 0.15% ~ 0.30%; Mn: 0.20% ~ 0.60%; Cr: 0.15% ~ 0.50%; P ≤ 0.020%; S ≤ 0.010%; the balance is Fe and unavoidable impurities; LX80ACr cord steel, C: 0.72% ~ 0.82%; Si: 0.15% ~ 0.30%; Mn: 0.20% ~ 0.60%; Cr: 0.15% ~ 0.50%; P ≤ 0.025%; S ≤ 0.015%; the balance is Fe and unavoidable impurities; LX80BCr cord steel, C: 0.72% ~ 0.82%; Si: 0.15% ~ 0.30%; Mn: 0.20% ~ 0.60%; Cr: 0.15% ~ 0.50%; P ≤ 0.020%; S ≤ 0.010%; the balance is Fe and unavoidable impurities; LX85BCr cord steel, C: 0.82% ~ 0.86%; Si: 0.15% ~ 0.30%; Mn: 0.20% ~ 0.60%; Cr: 0.15% ~ 0.50%; P ≤ 0.020%; S ≤ 0.010%; the balance is Fe and unavoidable impurities; LX90BCr cord steel, C: 0.86% ~ 0.92%; Si: 0.15% ~ 0.30%; Mn: 0.20% ~ 0.60%; Cr: 0.15% ~ 0.50%; P ≤ 0.020%; S ≤ 0.010%; the balance is Fe and unavoidable impurities; LX96BCr cord steel: C: 0.92% ~ 0.96%; Si: 0.15% ~ 0.30%; Mn: 0.20% ~ 0.60%; Cr: 0.15% ~ 0.50%; P ≤ 0.015%; S ≤ 0.010%; the balance is Fe and unavoidable impurities.
2. The method for improving the drawing performance of cord steel by Cr alloying according to claim 1, characterized in that: The properties of the LX70ACr cord steel are as follows: tensile strength of 1000-1120 MPa, elongation ≥10%, and cross-sectional shrinkage ≥40%.
3. The method for improving the drawing performance of cord steel by Cr alloying according to claim 1, characterized in that: The properties of the LX70BCr cord steel are as follows: tensile strength of 1000-1120 MPa, elongation ≥10%, and cross-sectional shrinkage ≥40%.
4. The method for improving the drawing performance of cord steel by Cr alloying according to claim 1, characterized in that: The properties of the LX80ACr cord steel are as follows: tensile strength of 1120-1250 MPa, elongation ≥10%, and cross-sectional shrinkage ≥38%.
5. The method for improving the drawing performance of cord steel by Cr alloying according to claim 1, characterized in that: The properties of the LX80BCr cord steel are as follows: tensile strength of 1120-1250 MPa, elongation ≥10%, and cross-sectional shrinkage ≥38%.
6. The method for improving the drawing performance of cord steel by Cr alloying according to claim 1, characterized in that: The properties of the LX85BCr cord steel are as follows: tensile strength ≥1127MPa, elongation ≥6%, and cross-sectional shrinkage ≥30%.
7. The method for improving the drawing performance of cord steel by Cr alloying according to claim 1, characterized in that: The properties of the LX90BCr cord steel are as follows: tensile strength ≥ 1130 MPa, elongation ≥ 5%, and cross-sectional shrinkage ≥ 25%.
8. The method for improving the drawing performance of cord steel by Cr alloying according to claim 1, characterized in that: The properties of the LX96BCr cord steel are as follows: tensile strength ≥ 1150 MPa, elongation ≥ 5%, and cross-sectional shrinkage ≥ 25%.